2012
DOI: 10.1016/j.ejvs.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The Basilic Vein and the Cephalic Vein Perform Equally in Upper Arm Arteriovenous Fistulae

Abstract: With the exception of the efferent vein diameter in the mid upper arm and operative time, there was no difference between a BC and BVT AVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…No. BCAVF Early failure (%) Secondary patency (%) Murphy et al 68 208 16 75 Zeebregts et al 69 100 11 79 Lok et al 70 186 9 78 Woo et al 71 71 12 66 Koksoy et al 72 50 8 87 Palmes et al 73 55 9 89 Ayez et al 74 87 8 83 Table 7. Early failure (within one month of access creation) and one year secondary patency rate of brachiobasilic AVF.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…No. BCAVF Early failure (%) Secondary patency (%) Murphy et al 68 208 16 75 Zeebregts et al 69 100 11 79 Lok et al 70 186 9 78 Woo et al 71 71 12 66 Koksoy et al 72 50 8 87 Palmes et al 73 55 9 89 Ayez et al 74 87 8 83 Table 7. Early failure (within one month of access creation) and one year secondary patency rate of brachiobasilic AVF.…”
Section: Referencementioning
confidence: 99%
“…No. BBAVF Early failure (%) Secondary patency (%) Murphy et al 68 74 3 75 Segal et al 75 99 23 64 Wolford et al 76 100 20 47 Arroyo et al 77 65 8 88 Keuter et al 78 52 2 89 Koksoy et al 72 50 8 88 Field et al 79 140 19 69 Ayez et al 74 86 6 73 Other variables that influence fistula use are: lower extremity atherosclerotic disease (LEAD), race and obesity. 90 Patients using calcium channel blockers, aspirin and ACE inhibitors, enjoy better AVF and AVG patency.…”
Section: Referencementioning
confidence: 99%
“…In our study, the basilic vein had larger diameters than the cephalic vein, but despite these differences there was no statistically significant difference in flow rates and steal scores. Although autogenous AVFs based on the cephalic and basilic vein also have similar primary and secondary patency, 12,13 the cephalic vein is preferred because the construction of a cephalic-based AVF requires a smaller operation.…”
Section: Discussionmentioning
confidence: 98%
“…A 2008 prospective randomized study of BCF versus BVT showed equivalent patency rates (8). More recently, a retrospective study examined 173 fistulae including BCF and BVT found similar patency rates between the two (9). In a randomized study of 105 patients comparing the patency rates of BVTs and prosthetic brachial antecubital forearm loops, BVTs had superior primary unassisted and primary assisted patency rates as well as decreased frequency of interventions (10).…”
Section: Discussionmentioning
confidence: 98%